Legislative Council debates - Gregory, Robert G. (Kenya Government Archives Photographic Service, 1965)
Contains debates of the Legislative Council for period 1907-1963 and debates of the National Assembly, House of Representatives for the period 1963 to 1965; originals held by the Kenya National Archives.